2015
DOI: 10.1007/s00259-015-3060-3
|View full text |Cite
|
Sign up to set email alerts
|

PET/MR brain imaging: evaluation of clinical UTE-based attenuation correction

Abstract: Our results indicate that the performance of the UTE method as implemented in VB20P is close to the theoretical maximum of such an MRAC method in the brain, while it does not perform satisfactorily in the neck or face/nasal area. Further improvement of the UTE MRAC or other available methods for more accurate segmentation of bone should be incorporated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
81
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(85 citation statements)
references
References 24 publications
2
81
2
Order By: Relevance
“…Second, ZTE requires minimal gradient switching, which can reduce eddy current effect. This might be some advantage when compared with the UTE-AC, which is one of the most popular segmentation-based methods in clinical head PET/MR study (8). The artifact sometimes causes the error in the calculation of T2 relaxation time on UTE-AC because of reduced signal intensities in the first UTE echo just after switching (9,29).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, ZTE requires minimal gradient switching, which can reduce eddy current effect. This might be some advantage when compared with the UTE-AC, which is one of the most popular segmentation-based methods in clinical head PET/MR study (8). The artifact sometimes causes the error in the calculation of T2 relaxation time on UTE-AC because of reduced signal intensities in the first UTE echo just after switching (9,29).…”
Section: Discussionmentioning
confidence: 99%
“…The first family is that of template-/atlas-/model-based approaches (5)(6)(7). The second one is that of segmentation approaches (8)(9)(10)(11)(12). The third one constitutes methods directly estimating attenuation information from emission data (13,14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The accuracy of the attenuation maps were evaluated using Dice similarity coefficients (40)(41)(42) that measure the overlap of the segmented bone and air regions of MR-AC maps with respect to those of CT-AC maps (1 for perfect overlap and 0 for no overlapping) according to the following equation:…”
Section: Image Analysismentioning
confidence: 99%
“…In brain PET/MRI imaging, ultrashort echo-time (UTE) (Keereman et al, 2010, Catana et al, 2010 and more recently zero echo-time (ZTE) , Delso et al, 2015 MR sequences have been developed to specifically delineate bones and include them in the attenuation maps. Initial UTE-based AC studies have reported quantification errors of less than 5% (Aasheim et al, 2015); however, the inhomogeneous and imprecise classification of bones, particularly in the presence of diamagnetic susceptibility effects at air/bone or air/soft-tissue interfaces (Delso et al, 2014) can give rise to errors in the range 4%-17% in different regions of the brain (Dickson et al, 2014). Recently, Delso et al (2015) demonstrated that ZTE-based bone segmentation outperforms its UTE-based counterpart with reduced segmentation errors.…”
Section: Introductionmentioning
confidence: 99%